Car lock indicator - Hairulazam, Hairuldin (2006)
Nowadays, car has become one of the most popular modes of transportation because many of Malaysians could afford to have a car. There are many choices of cars in the market, from budget cars to the luxurious cars, only a matter now is affordability. One of the important aspects of a car is security because car theft is a crime that occurs all around the world, including Malaysia. Currently, local car manufacturers in Malaysia provides a standard security system for each car manufactured, that is central locking system and standard car alarm. The focus is on the car locking system, where the conventional remote for the car locking system is commonly consists of two buttons, which is the first, is for lock and unlock function and the second button is for the car alarm. There is no indicator that indicates the lock status of the car, acting as the double confirmation for the lock status. Here comes the idea to improve the conventional car lock system by adding an indicator to work as the second confirmation for the car lock status. The project is named as Car Lock Indicator and using microcontroller Motorola MC68HC11A1 as the heart of the system. For the indicator, Light Emitting Diode (LED) is the most suitable because it is cheap, reliable, low voltage consumption thus makes the battery could last longer.